KNL1 is a prognostic and diagnostic biomarker related to immune infiltration in patients with uterine corpus endometrial carcinoma - He, Kang; Li, Jingze; Huang, Xuemiao; Zhao, Weixin; Wang, Kai; Wang, Taiwei; Chen, Junyu; Wang, Zeyu; Yi, Jiang; Zhao, Shuhua; Zhao, Lijing (Frontiers in Oncology, 2023)
Background: The incidence and mortality of uterine corpus endometrial carcinoma (UCEC) are increasing year by year. So far, there is no screening test for UCEC, and progress in its treatment is still lacking. It is important to identify new biomarkers for screening, diagnosis and prognosis. A large number of previous studies have proved that KNL1 is crucial in the development of lung cancer, colorectal cancer and cervical cancer, but there is a lack of studies to prove the role of KNL1 in the development of UCEC. Methods: The mRNA and protein expression data of KNL1 in the cancer genome atlas (TCGA), the Gene Expression Omnibus (GEO) and UALCAN databases and related clinical data were used to analyze the expression differences and clinical correlation of KNL1 in UCEC. A total of 108 clinical samples were collected and the results of bioinformatics analysis were verified by immunohistochemistry. KNL1 and its related differential genes were used to draw a volcano map, construct a PPI protein interaction network, and perform gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), Gene set enrichment analysis (GSEA) analysis and immune infiltration analysis to predict the function of KNL1 in the process of UCEC progression. The prognostic data of TCGA and 108 clinical patients were used to analyze the effect of KNL1 expression on the survival and prognosis of patients, and the KM survival curve was drawn. Finally, UCEC cell lines Ishikawa and Hec-1-A were used to verify the function. Results: KNL1 is significantly overexpressed in UCEC and leads to poor prognosis. KNL1 is closely related to cell mitosis, cell cycle and other functions, and is related to International Federation of Gynecology and Obstetric (FIGO) stage, Histological grade and other characteristics of UCEC patients. Knockdown of KNL1 expression in UCEC cell lines can inhibit their proliferation, invasion, metastasis and other phenotypes. Conclusion: KNL1 is a prognostic and diagnostic biomarker associated with immune invasion in patients with UCEC.